Hubungan Interaksi Guru dan Siswa dalam Proses Pembelajaran di SMA Negeri 1 Barabai - Ubaidillah (PT. Hasba Edukasi Mandiri, 2026)
This study aims to examine the level of interaction and relationship between teachers and students at SMA Negeri 1 Barabai, the factors influencing it, and the efforts to improve it. The background of this research is based on the phenomenon that teacher-student relationships vary; some teachers and students demonstrate high harmony in communication and mutual respect during learning, while others still experience problems such as awkwardness, lack of open communication during the learning process, and ineffective interaction management. This inconsistency is assumed to be influenced by intensive use of social media, low learning motivation, and lack of awareness in building professional yet empathetic communication.